Progress of Air Pollution Control in China and Its Challenges and Opportunities in the Ecological Civilization Era. (December 2020) - Lu, Xi; Zhang, Shaojun; Xing, Jia; Wang, Yunjie; Chen, Wenhui; Ding, Dian; Wu, Ye; Wang, Shuxiao; Duan, Lei; Hao, Jiming
Abstract: China's past economic growth has substantially relied on fossil fuels, causing serious air pollution issues. Decoupling economic growth and pollution has become the focus in developing ecological civilization in China. We have analyzed the three-decade progress of air pollution controls in China, highlighting a strategic transformation from emission control toward air quality management. Emission control of sulfur dioxide (SO2 ) resolved the deteriorating acid rain issue in China in 2007. Since 2013, control actions on multiple precursors and sectors have targeted the reduction of the concentration of fine particulate matter (PM2.5 ), marking a transition to an air-quality-oriented strategy. Increasing ozone (O3 ) pollution further requires O3 and PM2.5 integrated control strategies with an emphasis on their complex photochemical interactions. Fundamental improvement of air quality in China, as a key indicator for the success of ecological civilization construction, demands the deep de-carbonization of China's energy system as well as more synergistic pathways to address air pollution and global climate change simultaneously.